GCT-75. ISOLATED PITUITARY STALK THICKENING - Bennett, Julie; Nobre, Liana; Bouffet, Eric; Abla, Oussama; Wasserman, Jonathan; Ertl-Wagner, Birgit; Bartels, Ute (Neuro-oncology (Charlottesville, Va.), 2020)
Abstract OBJECTIVES Only few studies have examined the predictive factors and outcome of isolated pituitary stalk thickening (PST) in children. We aim to describe our institutional cohort to determine predictors of future malignancy. METHODS A search of the radiology, endocrinology and neuro-oncology databases was performed to identify patients with isolated PST diagnosed between January 2000 and June 2019. Clinical data was collected. A detailed radiology review of baseline and follow up magnetic resonance imaging (MRI) was undertaken in a blinded fashion by two examiners. RESULTS Forty-four patients were identified, with 37 meeting criteria for isolated PST and adequate imaging. Median age of baseline MRI was 9.9 years (range 0.9–17.5). Twenty-three were female (62%). Median follow up time was 5 (0.31–18.6) years. Indication for MRI was symptoms of diabetes insipidus (DI) in 28 patients with the remainder having other concerns for endocrine disturbance (7), headache (1) or visual impairment (1). Thirty-five subjects had pituitary dysfunction (95%), including 30 with diabetes insipidus (81%). Nine patients developed a malignancy (24%), with germinoma (5), Langerhans cell histiocytosis (3) and lymphoma (1) at a median of 0.36 years, 0.63 years and 1.1 years respectively. Elevated white blood cell count (>5 x 106/L) in initial cerebrospinal fluid analysis was predictive of future diagnosis of germinoma or lymphoma (p=0.027). CONCLUSION In this cohort 24% of children with PST were eventually diagnosed with a neoplasia after a median of 0.63 years. Pleocytosis in initial CSF samples was predictive for future development of germinoma or lymphoma.